Attention! This book will make you money : how to use attention-getting online marketing to increase your revenue - Kukral, Jim F. (Wiley, 2010)
"Attention! gives you an educational and motivational guide to using social media to market your brand or business online. In three parts, you'll discover everything you need to know to get off the ground and thrive in the social mediasphere."--Resource description page